Problem-Based Learning Assisted By Cre-ASI (Creative Assessment With Solving Instrument) to Improve Students' Creativity Thinking Skills - Dwikoranto; Dzulkiflih; Lintangesukmanjaya, Rahmatta Thoriq; Putra, Dedy Aufansyah; Bergsma, Lindsay N. (Jurnal Pendidikan IPA Indonesia, 2025)
This study aims to analyze the validity of the Cre-ASI instrument and its practicality and effectiveness when applied to PBL in improving creative thinking skills. The research design used the ADDIE model. The Analyze, Design, Development, Implementation, and Evaluation stages were used. The results of the Cre-ASI (Creative Assessment with Solving Instrument) instrument, which aims to improve creative thinking skills, have met the validity criteria and, when applied in PBL, meet the practical and effective criteria. The results of the Cre-ASI instrument development obtained a validity percentage value of 96.1%, which is a very valid category. When applying the instrument in PBL, a N-Gain score of 0.68 was obtained, and an increase in student answers was observed between the pre-test and post-test. The findings from the development of Cre-ASI in the PBL model revealed a positive correlation between indicators of problem-solving skills and creative thinking skills; students with low problem-solving skills tend to have low creativity. The integration of PBL and Cre-ASI has been shown to encourage knowledge construction, thinking strategies, learning motivation, and the development of students' cognitive abilities. This confirms that physics learning is not only focused on mastering concepts, but also on developing creativity and problem-solving skills. In the future, utilizing sophisticated technology to produce more efficient products with alternative costs and improved time and material efficiency is crucial, as this will enable the results of this study to serve as both an innovation and a benchmark in the selection and development of innovative assessment instruments in physics learning.